A biorefinery-based approach for the production of ethanol from enzymatically hydrolysed cotton stalks. (October 2017) - Christopher, Meera; Mathew, Anil K.; Kiran Kumar, M.; Pandey, Ashok; Sukumaran, Rajeev K.
Highlights: A complete process for the conversion of cotton stalk residue to bioethanol is described. The merits and demerits of acid and alkali pretreatment of CS have been explored. Enzyme/biomass recycling for biomass hydrolysis process was investigated. Fermentation using a novel strain of Saccharomyces cerevisiae with improved inhibitor tolerance. Abstract: Cotton post-harvest residue/cotton stalk (CS) – a major agro-residue in south asian countries was evaluated as a feed stock for bioethanol production. The common thermochemical pretreatment strategies based on dilute acid and alkali and different combinations of biomass hydrolyzing enzymes were evaluated for saccharification of CS biomass. A hydrolytic efficiency of 80% was achieved for alkali treated biomass using cellulase supplemented with beta glucosidase. Recycling of undigested/residual biomass and/or enzyme supported same final sugar concentration as for fresh hydrolytic experiments. Fermentation was carried out using a novel, inhibitor-resistant strain of Saccharomyces cerevisiae where 76% of theoretical maximum efficiency was attained. Material balances were derived for the entire process from biomass pre-processing to hydrolysis.